2003
DOI: 10.1210/jc.2003-030123
|View full text |Cite
|
Sign up to set email alerts
|

CYP21 Genotype, Adult Height, and Pubertal Development in 55 Patients Treated for 21-Hydroxylase Deficiency

Abstract: In a retrospective study we evaluated long-term growth, pubertal developmental patterns to final height (FH), and medication in 55 patients (35 females) affected by 21-hydroxylase deficiency. The patients were classified into 3 groups according to predicted mutation severity: group A (11 women and 9 men), homozygous or compound heterozygous for null or In2 splice mutations [residual enzymatic activity (RA), <1%]; group B (11 women and 4 men), homozygous for I172N or R341P or R426H mutations (RA, approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
52
1
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 24 publications
4
52
1
7
Order By: Relevance
“…We noted low final height compared with target height, consistent with former publications (25)(26)(27)(28), while the onset of pubertal height was normal. Height gain was also reported as poor during pubertal years in studies conducted by Stikkelbroeck et al (29) and van der Kamp et al (30).…”
Section: Discussionsupporting
confidence: 91%
“…We noted low final height compared with target height, consistent with former publications (25)(26)(27)(28), while the onset of pubertal height was normal. Height gain was also reported as poor during pubertal years in studies conducted by Stikkelbroeck et al (29) and van der Kamp et al (30).…”
Section: Discussionsupporting
confidence: 91%
“…who showed a positive correlation of FHZ and height at 2 years of age in salt-losing patients (21), the present study corroborates that height loss occurs mainly within the first two years of life. In addition, some reports showed that FH was greater in patients with early treatment, up to 20 months (24) and before 3 years of CA (20), although these data are controversial among the authors (3,23). In this study, a group of patients who initiated treatment early reached their TH.…”
Section: Discussionmentioning
confidence: 73%
“…Studies evaluating GC effect during childhood evidenced a negative influence of the daily dose of GC upon growth velocity and FH in children up to one or two years of CA and in prepubertal children (11,(20)(21)(22)(23). Similar to Manoli and cols.…”
Section: Discussionmentioning
confidence: 87%
“…The members of this family with NC CAH (father, sister) were only detected as a consequence of the presentation of the proband with SW CAH. The father had early puberty and diminished adult height which has been reported in NC CAH 40 " 44 .…”
mentioning
confidence: 66%